The Great Crisis of Collectivisation in the Pardubice Region (Theatrum historiae, 2015)
After Stalin’s and Gottwald’s death in March 1953 political changes occurred in the states of Eastern Bloc. These essential changes were called the New Course, which put emphasis on political liberation of regimes and an increase of standard of living. The crisis of collectivisation started at the same time in Czechoslovakia and the Pardubice Region. The Tenth Congress of the Communist Party of Czechoslovakia held in June 1954 was very important for further development of agriculture. The state provided support for peasants in collective farms, as well as in the private sector. The increase of agriculture production, broadening of arable land and the comeback of workers, who had been recruited to factories, back to agriculture were among the most important directives of the Tenth Congress. Nevertheless, the application of the congressional directives was refused by the national committee and communist party organization on lower level.
Keywords: Crisis; collectivisation; the New Course; the Tenth Congress of the Communist Party of Czechoslovakia; Pardubice Region; collective farms; collective farm members; peasants; agriculture production